Gerakan Ihya’ As-Sunnah Sedekah Nasi Jum’at Di Masjid Nur Farhan Papringan, Sleman Yogyakarta (Sebuah Kajian Living Qur’an): Indonesia - Sugiarto, Fitrah; Nikmatullah, Nikmatullah; Sa’i, Muhammad (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2023)
The study of the living Qur'an is one of the studies in the form of scientific research that concentrates on the social events of muslim society by making the Qur'an as an object and subject in everyday life. By paying attention to social phenomena, it will appear a continuous process of interaction between the Qur'an and the community. This study uses a qualitative approach with descriptive method of analysis. So that the data is obtained through books, journals and articles related to the discussion. The results showed that, Living Qur'an is the result of the orientation of the social phenomenon of the community with the Qur'an that displays the Qur'an in Everyday Life, which in a sense both in text, function and then the Qur'an in the practice of the muslim community directly in their daily lives. One example that can be seen is the practice of Friday rice alms by Nur Farhan Papringan Mosque as a form of Ihya’ As-Sunnah movement which later became a study of the living Qur'an. The movement of Ihya ' As-Sunnah in the form of Friday rice alms departs from the word of Allah Qs. Al-Hadid verse 18 which discusses the reward from Allah for a servant who gives charity, and departs from the hadiths of the Prophet. This tradition then emerged in society as a form of participation of human consciousness to help each other to help each other.